2011
DOI: 10.1128/jvi.05213-11
|View full text |Cite
|
Sign up to set email alerts
|

Annual Vaccination against Influenza Virus Hampers Development of Virus-Specific CD8+T Cell Immunity in Children

Abstract: Infection with seasonal influenza A viruses induces immunity to potentially pandemic influenza A viruses of other subtypes (heterosubtypic immunity).We recently demonstrated that vaccination against seasonal influenza prevented the induction of heterosubtypic immunity against influenza A/H5N1 virus induced by infection with seasonal influenza in animal models, which correlated with the absence of virus-specific CD8 ؉ T cell responses. Annual vaccination of all healthy children against influenza has been recomm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 46 publications
6
66
1
Order By: Relevance
“…There is evidence from animal studies that repeated vaccination can interfere with the development of cross-reactive immunity against other subtypes, likely mediated by reduced virusspecific CD8+ T cell response [51,52]. In children, annual vaccination has also been demonstrated to hamper development of virus-specific CD8+ T cell immunity [53]. The implications remain unclear, but these findings raise the possibility that repeated vaccination of low-risk individuals could affect the occurrence or severity of illness caused by a new pandemic virus or a new seasonal virus antigenic cluster.…”
Section: Possible Immune Mechanisms For Repeated Vaccination Effectsmentioning
confidence: 99%
“…There is evidence from animal studies that repeated vaccination can interfere with the development of cross-reactive immunity against other subtypes, likely mediated by reduced virusspecific CD8+ T cell response [51,52]. In children, annual vaccination has also been demonstrated to hamper development of virus-specific CD8+ T cell immunity [53]. The implications remain unclear, but these findings raise the possibility that repeated vaccination of low-risk individuals could affect the occurrence or severity of illness caused by a new pandemic virus or a new seasonal virus antigenic cluster.…”
Section: Possible Immune Mechanisms For Repeated Vaccination Effectsmentioning
confidence: 99%
“…These children received influenza vaccine annually, compared with previously unvaccinated healthy children. 8 Annual influenza vaccination with IIV was shown to hamper the development of virus- specific CD8C T cell responses. However, a review article by Belshe et al 9 showed that LAIV efficacy did not decrease with increasing pre-existing immunity to influenza in children 15 to 84 months of age compared with placebo or in children 6 months to 17 years of age compared with trivalent IIV.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns have been raised from animal data that early and repeated vaccination with nonadjuvanted inactivated vaccines may interfere with heterosubtypic immunity and therefore increase susceptibility to illness with heterotypic strains. [187,188] This might be of particular concern in the setting of the emergence of pandemic influenza viruses. However, the theoretical dangers of early and repeated vaccination of children are outweighed by the disease reduction associated with protection against currently circulating subtypes.…”
Section: Vaccine Effectiveness In Children Younger Than 2 Yearsmentioning
confidence: 99%